Surgery plus anesthesia induces loss of attention in mice - Ren, Quan; Peng, Mian; Dong, Yuanlin; Zhang, Yiying; Chen, Ming; Yin, Ning; Marcantoni, Edward; Xie, Zhongcong (Frontiers in Cellular Neuroscience, 2015)
There is a need to develop animal models to study postoperative delirium. Inattention is one of the symptoms of delirium. Increases in the levels of α-synuclein and S100β have been reported to be associated with delirium. Therefore, we set out to determine the effects of surgery plus general anesthesia on the behavioral changes (including loss of attention) in mice and on the levels of α-synuclein and S100β in the brain tissues of these mice. C57BL/6J mice (2- to 8-months-old) had a simple laparotomy plus isoflurane anesthesia. The behavioral changes, including attention level and the speed of movements, were determined 12, 24 and 48 hours after the surgery plus anesthesia in the mice. The levels of α-synuclein and S100β in the cortex of these mice following the surgery plus anesthesia were determined by Western blot analysis. We found that there was a loss of attention at 24, but not 12 or 48, hours following the surgery plus anesthesia (49%+5 versus 33%+2.9, P=0.011, N=12) in the mice without significantly affecting the speed of their movements. There were increases in the levels of total α-synuclein (139%+33.5 versus 100%+13.7, P=0.037, N=6) and S100β (142%+7.7 versus 100%+6, P=0.002, N=6) in the cortex of the mice 12 hours following the surgery plus anesthesia. These findings suggested that the surgery plus isoflurane anesthesia might induce behavioral and biochemical/biochemical/cellular changes associated with delirium. We could use the surgery plus anesthesia in mice to develop an animal model to study postoperative delirium.